Interleukin-33 Expression Indicates a Favorable Prognosis in Malignant Salivary Gland Tumors. (August 2016) - Rössle, Matthias; Cathomas, Gieri; Bonapace, Laura; Sachs, Melanie; Dehler, Silvia; Storz, Martina; Huber, Gerhard; Moch, Holger; Junt, Tobias; Mertz, Kirsten D.
The cytokine interleukin-33 (IL-33) is abundantly expressed in epithelial barrier tissues such as salivary glands. Here, we characterized nuclear IL-33 protein expression by immunohistochemistry in benign and malignant salivary gland tumors and associated it with disease outcome. Most benign salivary gland tumors expressed IL-33, and all Warthin's tumors showed strong and consistent IL-33 expression in the basally oriented cells of their bilayered epithelium. In the malignant group of neoplasms, nuclear IL-33 expression was limited to specific tumor entities—for example, to epithelial-myopepithelial carcinomas (n = 9/11), acinic cell carcinomas (n = 13/27), and oncocytic carcinomas (n = 2/2). IL-33 expression in the combined group of malignant salivary gland neoplasms was significantly associated with favorable histological parameters, lack of metastasis, and longer overall survival, compared with IL-33–negative tumors. We conclude that IL-33 expression is a novel prognostic marker for malignant salivary gland tumors with potential use in clinical diagnostics.